PERLINDUNGAN PEKERJA MENURUT HUKUM ISLAM (Analisis terhadap Al-Qur’an dan Hadits) - Muhammad Arsad Nasution (Institut agama islam negeri Padangsidimpuan, 2019)
This paper describes the protection of workers according to Islamic law by analyzing several verses of the Qur'an and the Hadith of the Prophet. There are many verses of the Koran that generally command good to others, as in Surah Al-Qashash verse 77, one form of good deeds is to provide protection to workers as an important component in providing benefits to the company. The Prophet's hadith also came to clarify the importance of good behavior by providing protection to workers. He strictly forbids giving physical punishment to workers, giving heavy work that cannot be done by work, and other physicalist pressures. Instead he cited good behavior towards workers as he treated his servants well